RELATIONSHIP BETWEEN WORK MOTIVATION AND WORK SATISFACTION OF NURSES IN THE CENTRAL SURGERY INSTALLATION OF DR SAIFUL ANWAR HOSPITAL, MALANG - Bagus Widya; Achmad Dafir Firdaus; Kurnia Laksana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
The evaluation of the performance of nurses in hospitals should take into account the crucial factor of job satisfaction. Motivation has the potential to influence job satisfaction. The objective of this study was to ascertain the relationship between work motivation and job satisfaction among nurses at the Central Surgical Installation of Dr. Saiful Anwar Hospital in Malang. The research design employed was that of a correlational study, examining the relationship between variables. The cross-sectional approach was utilised. The study population comprised all nurses employed at the Central Surgical Installation Room (IBS) of Dr. Saiful Anwar Hospital in Malang, amounting to a total of 72 nurses. The sample size was determined using the Slovin formula and consisted of 42 nurses. The sampling technique employed was quota sampling. The data were collected via a questionnaire. The results demonstrated that the Somers' D correlation coefficient was 0.222, thereby accepting H1 (p-value <0.05). The Somers correlation coefficient is positive, indicating that as motivation increases, job satisfaction among nurses in the Central Surgical Installation of Dr. Saiful Anwar Hospital in Malang also rises. In light of the findings, it is recommended that the hospital implement strategies to enhance the motivation of nurses. One potential approach is the introduction of work motivation improvement programmes, such as refresher courses, to facilitate mutual understanding between superiors, subordinates, and colleagues. This could potentially lead to an improved work environment, greater job satisfaction, and enhanced job performance.